The role of procurement in creating supply chain resilience - Pereira, Carla Roberta (2014)
Achieving resilience along the supply chain in today's turbulent business environment requires efforts from both internal and external elements of the company. Because Procurement is currently considered a boundary spanning function, it has become a primary facilitator in helping to create supply chain resilience. The purpose of this study is therefore to understand the role of Procurement in managing the intra- and inter-organisational issues needed to create supply chain resilience. To do so, a literature review was developed by following the systematic literature review method in which intra- and inter-organisational issues that could impact supply chain resilience were identified. These issues were grouped into eight general topics: knowledge acquired, inventory, product and technology for intraorganisational issues; and strategic sourcing, supply chain design, transportation and risk for inter-organisational issues. Dynamic capability (DC) view was also reviewed to offer a deeper analysis and fresh perspective on the empirical results. A multiple case study was conducted in four focal companies from different sectors, including two key suppliers from each one. After all interviews were transcribed, the data was added to the QDA Miner software in order to conduct a content analysis of within-cases and, subsequently, cross-case analysis. Following the theory elaboration defined by Ketokivi and Choi (2014), propositions were developed based on the empirical and theoretical findings through the rationale of the dynamic capability view. As a result, procurement structure and external inventory were found as additional organisational issues, and a new rationale is proposed to explain how Procurement can create supply chain resilience through dynamically managing and controlling the identified organisational issues. The primary theoretical contribution of this research is applying a new perspective to the issue of resilience. The development of these capabilities may help Procurement managers to better cope with current critical supply disruptions and hence help to achieve company survival and competitiveness.